More than Ownership: The Importance of Relationships with Companion Dogs for the Psychological Adjustment of Fibromyalgia Patients. Issue 12 (16th February 2021) - Silva, Karine; Castro, Luísa; Costa-Santos, Cristina; Lourenco, Antonio; Lima, Mariely
Abstract: Objective: This study explored the role of companion dogs for psychological adjustment to pain in patients with fibromyalgia with different levels of social support. It also considered the potential moderating effects of the quality of the owner-dog relationship and the use of interactions with dogs as a coping strategy. Setting: A cross-sectional approach was followed using an online questionnaire. Subjects and Methods: Linear regression analyses were performed on data obtained from 106 participants (dog owners and non-owners). Sub-analyses were performed on 64 dog owners. Results: Complex associations were observed between human social support, dog ownership and anxiety/depression levels. For participants with low levels of social support, owning a dog was associated with higher levels of anxiety and depression. In contrast, for moderate and high levels of social support, owning a dog was associated with lower levels of anxiety and depression. Sub-analyses showed that participants in this study actively used interactions with companion dogs to manage their pain more frequently than other pain coping strategies. Among those interactions, patting and stroking the dog to cope with pain was associated with lower anxiety levels, even after adjusting for social support. Emotional closeness with the dog was associated with lower depression levels. Conclusions: Obtained results highlight the importance to go beyond mere ownership when addressing the effects of companion dogs and suggest that the development of emotional ties with companion dogs and the active use of interactions with these animals to cope with pain may contribute to better psychological adjustment in patients with fibromyalgia, regardless of human social support.